The strategic impact of external networks: subsidiary performance and competence development in the multinational corporation - Andersson, Ulf; Forsgren, Mats; Holm, Ulf (Strategic Management Journal, 2002)
Abstract This paper explores the importance of relational embeddedness in external networks as a strategic resource for performance and competence development in multinational corporations (MNCs). Two different types of relational embeddedness at the subsidiary level—business embeddedness and technical embeddedness—are proposed to have an influence on the subsidiary's market performance as well as its importance for competence development in the MNC. Using data on 97 Swedish MNC subsidiaries, five hypotheses are tested in a LISREL model analysis. The results suggest that technical embeddedness has a positive impact on both the subsidiary expected performance and its role in the development of products and production processes in the MNC. Indirectly, through external technical embeddedness, external business embeddedness also influences the sister units' product and process development and subsidiary market performance. Copyright © 2002 John Wiley & Sons, Ltd.